A SYSTEMATIC REVIEW OF THE ASSOCIATION BETWEEN ERYTHROCYTE INDICES AND STAGES OF CHRONIC KIDNEY DISEASE - Tan, Cindy; Bororing, Sheella Rima; Iryaningrum, Maria Riastuti (Indonesian Journal of Urology, 2022)
Objective: To obtain the association between the erythrocyte indices and the stages of CKD. Material & Methods: This is a systematic review study conducted by searching for articles through PubMed, Proquest, and Google Scholar. Publication year are from 2010 to 2020. Results: There are 10 articles analyzed. There were 3 articles that showed a significant association and 2 articles that showed no significant association between erythrocyte indices and stages of CKD. Other article that used anemia morphology to represent the erythrocyte indices showed the normocytic normochromic as the largest percentage. 4 out of 5 articles with CKD patients who were known to be undergoing hemodialysis showed a significant difference in erythrocyte indices. Conclusion: There is association between the erythrocyte indices and stages of CKD.